(untitled) (Journal of Forensic Medicine & Toxicology, 2022)
Aluminium(Al) is a naturally occurring trace element that makes up about 8% of the surface of earth. It is used in cooking utensils, containers, appliances, and building materials. It is also used in paints and fireworks, to produce glass, rubber and ceramics, and in consumer products such as antacids, astringents, buffered aspirin, food additives, and antiperspirants. Normal levels of Al in blood are <5.41µg/L.Blood aluminium levels in patients with acute Al toxicity are 400-1,000µg/L and in patients of Al encephalopathy is 150-300µg/L. This study was carried out to know the prevalence & distribution of these metals in general population so as to help in investigation of alleged deaths due to aluminium toxicity and its related compounds poisoning. The level of aluminium in blood, liver and stomach contents in 100 bodies brought for medicolegal autopsy at AIIMS, New Delhi were estimated with help of Inductively Coupled Plasma -Atomic Emission Spectrometry (ICP- AES)during the period of march 2014 to march 2016. It was found that the mean blood aluminium levels were 4.58 ìg/ml with range of 0-24 ìg/ml. The mean aluminium levels in liver and stomach contents were 5.95 ìg/g with a range of 0–49.88 ìg/g and 82.50 ìg/ml with a range of 0 – 7582.59 ìg/ml respectively.